Green Teeth Related to Bilirubin Levels - Gabriel S. Barbério; Ana C. G. Zingra; Paulo S. S. Santos; Maria A. A. M. Machado (University of Zagreb. School of Dental Medicine, 2018)
Objective: To describe a form of tooth pigmentation caused by serum bilirubin deposition during dental calcification in a premature child. The bilirubin levels during the three months after birth are presented. In this period the crowns of the primary teeth are still forming. Such anomaly does not have symptoms, but has a displeasing effect and great anxiety within the family. Case report: The case reported here highlights the relevance of past medical history, especially the diagnoses of prolonged conjugated hyperbilirubinemia, in this case, to confirm them and to comfort the family. In this case, no esthetic treatment had been undertaken because the child was still too young and not yet concerned. The dental treatment plan included regular checkups every 3 months for maintaining oral health to prevent caries. Conclusion: As this is a rare condition that affects the teeth, parents will most likely look for a dentist for treatment. Therefore, dentists must be aware or such abnormalities and take a multidisciplinary approach, thus making it possible to establish a final diagnosis.